Aging in Rats Differentially Affects Markers of Transcriptional and Translational Capacity in Soleus and Plantaris Muscle - Mobley, Christopher B.; Mumford, Petey W.; Kephart, Wesley C.; Haun, Cody T.; Holland, Angelia M.; Beck, Darren T.; Martin, Jeffrey S.; Young, Kaelin C.; Anderson, Richard G.; Patel, Romil K.; Langston, Gillis L.; Lowery, Ryan P.; et al. (Frontiers in Physiology, 2017)
Alterations in transcriptional and translational mechanisms occur during skeletal muscle aging and such changes may contribute to age-related atrophy. Herein, we examined markers related to global transcriptional output (i.e., myonuclear number, total mRNA and RNA pol II levels), translational efficiency [i.e., eukaryotic initiation and elongation factor levels and muscle protein synthesis (MPS) levels] and translational capacity (ribosome density) in the slow-twitch soleus and fast-twitch plantaris muscles of male Fischer 344 rats aged 3, 6, 12, 18 and 24 months (n=9-10 per group). We also examined alterations in markers of proteolysis and oxidative stress in these muscles (i.e., 20S proteasome activity, poly-ubiquinated protein levels and 4-HNE levels). Notable plantaris muscle observations included: a) fiber cross sectional area (CSA) was 59% (p<0.05) and 48% (p<0.05) greater in 12 month versus 3 month and 24 month rats, respectively, suggesting a peak lifetime value near 12 months and age-related atrophy by 24 months, b) MPS levels were greatest in 18 month rats (p<0.05) despite the onset of atrophy, c) while regulators of ribosome biogenesis [c-Myc and upstream binding factor (UBF) protein levels] generally increased with age, ribosome density linearly decreased from 3 months of age and RNA polymerase (Pol) I protein levels were lowest in 24 month old rats, and d) 20S proteasome activity was robustly up-regulated in 6 and 24 month rats (p<0.05). Notable soleus muscle observations included: a) fiber CSA was greatest in 6 month rats and was maintained in older age groups, and b) 20S proteasome activity was modestly but significantly greater in 24 month versus 3/12/18 month rats (p<0.05), and c) total mRNA levels (suggestive of transcriptional output) trended downward in older rats despite non-significant between-group differences in myonuclear number and/or RNA Pol II protein levels. Collectively, these findings suggest that plantaris, not soleus, atrophy occurs following 12 months of age in male Fisher rats and this may be due to translational deficits (i.e., changes in MPS and ribosome density) and/or increases in proteolysis rather than increased oxidative stress and/or alterations in global transcriptional mechanisms.